2022
DOI: 10.1002/rcm.9324
|View full text |Cite
|
Sign up to set email alerts
|

Method development for determination of polyhalogenated carbazoles in industrial waste through gas chromatography/triple quadrupole tandem mass spectrometry

Abstract: Rationale Polyhalogenated carbazoles (PHCZs) are dioxin‐like compounds that are ubiquitous in the environment. However, their unintentional emissions from industrial sources have received little attention and there is no method available for determination of PHCZs in industrial waste. This research develops a method for determination of PHCZs in industrial waste. Methods In this research, a glass column packed with activated silica serves as a rapid and efficient clean‐up pretreatment for purification. An isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The LOD (all expressed in ng/mL) of CZL-HPCD obtained in the present study is better, more economical, and straightforward than some others reported by fluorescence with derivatization reaction in TLC ] and in the same order than with a clean-up on a silica gel column GC/MS/MS (1) [51]. Some others report better LOD by SPE-RTP with a laborious procedure(0.015) [36], or with SPE-GC-MS, depending on the type of SPE (10 32 and 1 31 ).…”
Section: Analytical Parameterssupporting
confidence: 47%
“…The LOD (all expressed in ng/mL) of CZL-HPCD obtained in the present study is better, more economical, and straightforward than some others reported by fluorescence with derivatization reaction in TLC ] and in the same order than with a clean-up on a silica gel column GC/MS/MS (1) [51]. Some others report better LOD by SPE-RTP with a laborious procedure(0.015) [36], or with SPE-GC-MS, depending on the type of SPE (10 32 and 1 31 ).…”
Section: Analytical Parameterssupporting
confidence: 47%
“…Thus, current research on source identification is woefully inadequate and does not support any reasonable explanation of the abundant residues, wide distribution, and complicated congener profiles of PHCZs in the environment 14 . Artificial sources of PHCZs remain unresolved but urgently need to be identified for emission control and pollution management [24][25][26] .…”
mentioning
confidence: 99%